Similar trends of susceptibility in Anopheles arabiensis and Anopheles pharoensis to Plasmodium vivax infection in Ethiopia - Abduselam, Nuredin (Parasit Vectors, 2016)
BACKGROUND: Around half of the global population is living in areas at risk of malaria infection. Plasmodium vivax malaria has become increasingly prevalent and responsible for a high health and socio-economic burden in Ethiopia. The availability of gametocyte carriers and mosquito species susceptible to P. vivax infection are vital for malaria transmission. Determining the susceptibility of vector species to parasite infection in space and time is important in vector control programs. This study assesses the susceptibility of Anopheles arabiensis, An. pharoensis and An. coustani group to Plasmodium vivax infection in Ethiopia. METHODS: Larvae of An. arabiensis, An. pharoensis and An. coustani group were collected from an array of breeding sites and reared to adult under controlled conditions. Batches of adult female mosquitoes of the three species were allowed to feed in parallel on the same infected blood with gametocytes drawn from Plasmodium vivax infected patients by Direct Membrane Feeding Assays (DMFA). Fed mosquitoes were kept in an incubator under controlled laboratory conditions. Seven days after each feeding assay, mosquitoes were dissected for midgut oocyst microscopy and enumeration. Data were analysed using R statistical software package version 3.1.0. RESULTS: Over all, 8,139 adult female mosquitoes were exposed to P. vivax infection. Of the exposed mosquitoes 16.64 % (95 % CI: 1,354–8,139) were properly fed and survived until dissection. The infection rate in An. arabiensis and An. pharoensis was 31.72 % (95 % CI: 28.35–35.08) and 28.80 % (95 % CI: 25.31–32.28), respectively. The intensity of infection for An. arabiensis and An. pharoensis was 2.5 (95 % CI: 1.9–3.2) and 1.4 (95 % CI: 1.1–1.8), respectively. Gametocyte density was positively correlated to infection rate and intensity of infection in An. arabiensis as well as An. pharoensis. No An. coustani group mosquitoes were found infected, though almost four hundred mosquitoes were successfully fed and dissected. All groups received blood from the same infected blood source containing gametocytes in parallel. There was no significant difference in susceptibility rates between An. arabiensis and An. pharoensis (P = 0.215). CONCLUSIONS: Anopheles arabiensis and An. pharoensis showed similar susceptibility to P. vivax infection. However, An. coustani group was not permissive for the development of P. vivax parasites.